Niosomes: an extensive analysis of its structure, preparation, and uses in drug delivery - Vaishali Sharma; Chinkey Mittal; Shweta Shekhedwal; Vasu Chaudhary; Sachin Kumar (Journal of Applied Pharmaceutical Research)
Background: Niosomes are sophisticated drug delivery vehicles composed of non-ionic surfactants that have a lot of potential for delivering drugs. Their unique bilayer structure enables the targeted and regulated release of both fat-soluble and water-soluble medications, enhancing their stability and absorption. This review discusses the components, production processes, benefits, drawbacks, and potential uses of niosomes in various medical fields, including cutaneous medication delivery and cancer treatment. Objective: This article provides an in-depth overview of niosomes as novel drug delivery vehicles, highlighting their benefits, preparation techniques, applications, and assessment criteria. It aims to highlight how they can improve therapeutic efficacy and bioavailability across various medicinal domains. Methodology: This article outlines multiple techniques employed in the preparation of niosomes, including the ether injection method, sonication method, hand-shaking method, extrusion method, thin film hydration, microfluidization method, and Transmembrane pH gradient drug uptake process. It also examines elements that impact niosome synthesis, such as the kind of surfactant utilized, the drug's characteristics, and environmental conditions. Conclusion: Ongoing research is focused on enhancing niosomal formulations and expanding their use in clinical settings, despite challenges such as instability and a short shelf life. Overall, niosomes are a significant development in drug delivery technology, with the potential to enhance treatment effectiveness and improve patient care.